New Practices of Tourism Industry as Effects of Development of the Agricultural Land Market - KULMAGANBETOVA, Aisulu; RUSTEMBAEV, Bazarkhan; MISNIK, Olessya; BAYARLIN, Almaz; RAMAZANOVA, Shynar; BEKTENOV, Samat (Journal of Environmental Management and Tourism; Vol 13 No 8 (2022): JEMT, Volume XIII, Issue 8(64), Winter 2022DO - 10.14505/jemt.v13.8(64).26, 2022)
The aim of this study is to identify and analyze new practice of the tourism industry which are in deep relation with the agricultural land market. The development of the agricultural land market causes an intensification of its role in the tourism industry, contributing also to the enhancement of other tourism sub-sectors, such as eco-agricultural tourism, rural tourism, eco-tourism, forest tourism industry, so it is a good reason to boost the need to establish a positive relationship between these two different types of land use. The tourism industry provides 10% of the turnover of the production and service market of the planet through the national product, investments, consumer spending, tax revenues and the organization of new jobs. This is facilitated by natural resources of each country, their hospitality, cultural and ethnic diversity, their individual tourist infrastructure with their burden of change and improvement within each country. Kazakhstan is rich in natural resources, has huge agricultural areas with a full range of agricultural destinations but also for other kind of activities which that can generate income, such are tourism activities